Pengaruh Kualitas Layanan dan Kepercayaan Terhadap Keputusan Loyalitas Nasabah - Rosa Jatnika Sari; Ine Aprianti (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2020)
The purpose of this study was to determine the effect of service quality, trust and loyalty.. The methodology of data collection is conducted through a questionnaire using a Likert scale. The population is the customer of Bank Negara Indonesia and the samples are taken from 84 respondents. The analysis includes validity test, reliability test, statistical test, classic assumption test and SPSS test. The findings from SPSS 20 statistic program tool show the independent variable test which is service quality and trust (X) is 0.750 or 75%. The results of multiple linear equations show that there is a positive and significant impact between service quality on customer loyalty, t count of 12,331 which means t count>t table (12,331>1,66365) with a significance of 0,000<0,05. The trust variable of t count is 11,147 which means t count>t table (11,147>1,66364) with a significance of 0.000<0,05. Individually, the service quality and trust have positive and significant impact on customer’s loyalty. It means the impact of independent variable (X) on dependent variable which is customer’s loyalty (Y) is 75%, while the rest 25% (100-75=25) is explained by another variable outside this research.